An Applied Research on the Compound Air Conditioning System of Ground Source Direct Cooling System and Water Storage Tank System. (2016) - Liu, Jiying; Qin, Fenghua; Xie, Xiaona; Zhang, Linhua
Abstract: Energy is an important material basis for China's economic and social development. The green building with the rule of energy saving and environmental protection and the reasonable and efficient air-conditioning systems arises at the historic moment. A Compound Air Conditioning System (CACS) of Ground Source Direct Cooling (GSDC) system and Water Storage Tank System (WSTS) is applied in an clod area and in details presented. The monitored data shows that the average operating cost of the air conditioning each year is lower than 10 Chinese yuan/m 2 . Therefore, this CACS system has a great potentiality in the demand of building energy saving in the cold areas.